1993
DOI: 10.1111/j.1398-9995.1993.tb02408.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of soluble ICAM‐1 in sera from patients with bronchial asthma

Abstract: We measured the levels of soluble intercellular adhesion molecule-1 (sICAM-1) in sera from patients with bronchial asthma. sICAM-1 levels in sera from atopic asthmatic patients in stable conditions were higher than in normal control subjects. Furthermore, the sICAM-1 levels in sera obtained during bronchial asthma attacks were higher than those in sera obtained in stable conditions. These results suggest that higher levels of sICAM-1 in sera reflect the upregulation of ICAM-1 expression in allergic inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 7 publications
6
27
1
Order By: Relevance
“…We also found highly significant correlations between serum sICAM–1 levels and the physiological parameters (RR, PEFR, O 2 % and PaCO 2 ) on which our assessment of the severity of asthma exacerbation was based. Hashimoto et al [15]in their study conducted on adult asthmatics found that serum sICAM–1 levels in sera obtained during bronchial asthma attacks were higher than those in sera obtained from stable asthmatic or normal subjects, which is similar to our observations. Furthermore, they found that serum sICAM–1 levels in atopic asthmatic patients in stable conditions were higher than in normal controls.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…We also found highly significant correlations between serum sICAM–1 levels and the physiological parameters (RR, PEFR, O 2 % and PaCO 2 ) on which our assessment of the severity of asthma exacerbation was based. Hashimoto et al [15]in their study conducted on adult asthmatics found that serum sICAM–1 levels in sera obtained during bronchial asthma attacks were higher than those in sera obtained from stable asthmatic or normal subjects, which is similar to our observations. Furthermore, they found that serum sICAM–1 levels in atopic asthmatic patients in stable conditions were higher than in normal controls.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast to our results and the aforementioned studies [14, 15, 20], Ceyhan et al [22]suggested that serum sICAM–1 levels are not increased in asthmatic patients as compared with controls and do not correlate with clinical asthma severity. These differences may be explained by multiple factors, notably the very small number of patients enrolled in their study (15 asthmatic patients and 5 controls), adults versus children, and their asthmatic patients had a relatively stable asthma.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Levels of serum sICAM-1 and soluble E-selectin (sE-selectin) are higher in stable asthmatics as compared with controls, and are further increased in acute asthma [87][88][89]. A rise in sICAM-1 occurs both in the serum and BAL of atopic asthmatics 18 h after allergen challenge [90].…”
Section: Icam-1 In Allergic Inflammation and Asthmamentioning
confidence: 99%